Ultracytochemical localization of the vacuolar marker enzymes alkaline phosphatase, adenosine triphosphatase, carboxypeptidase Y and aminopeptidase reveal new concept of vacuole biogenesis in Saccharomyces cerevisiae - Vorísek, J (Histochemistry, 1989)
Logarithmic cultures of Saccharomyces cerevisiae strains LBG H 1022, FL-100, X 2180 1A and 1B were studied together with the mutants pep4-3, sec18-1 and sec7-1. The necessary ultrastructural observations showed that, as a rule, juvenile vacuoles were formed de novo from perinuclear endoplasmic reticulum cisternae (ER) packed and inflated with electron-dense (polyanionic) matrix material. This process was disturbed solely in the sec18-1 mutant under non-permissive conditions. The vacuolar marker enzymes adenosine triphosphatase (ATPase) and alkaline phosphohydrolase (ALPase) were assayed by the ultracytochemical cerium precipitation technique. The neutral ATPase was active in vacuolar membranes and in the previously shown (coated) microglobules nearby. ALPase activity was detected in microglobules inside juvenile vacuoles, inside nucleus and in the cytoplasm as well as in the membrane vesicles and in the periplasm. The sites of vacuolar protease carboxypeptidase Y (CPY) activity were assayed using N-CBZ-L-tyrosine-4-methoxy-2-naphthyl-amide (CBZ-Tyr-MNA) as substrate and sites of the amino-peptidase M activity using Leu-MNA as substrate. Hexazotized p-rosaniline served as a coupler for the primary reaction product of both the above proteases (MNA) and the resulting azo-dye was osmicated during postfixation. The CPY reaction product was found in both polar layers of vacuolar membranes (homologous to ER) and in ER membranes enclosing condensed lipoprotein bodies which were taken up by the vacuoles of late logarithmic yeast. Both before and after the uptake into the vacuoles the bodies contained the CPY reaction product in concentric layers or in cavities. Microglobules with CPY activity were also observed. Aminopeptidase was localized in microglobules inside the juvenile vacuoles. These findings combined with the previous cytochemical localizations of polyphosphates and X-prolyl-dipeptidyl (amino)peptidase in S. cerevisiae suggest the following cytologic mechanism for the biosynthetic protein transport: coated microglobules convey metabolites and enzymes either to the cell surface for secretion or enter the vacuoles in all phases of the cell cycle. The membrane vesicles represent an alternative secretory mechanism present in yeast cells only during budding. The homology of the ER with the vacuolar membranes and with the surface membranes of the lipoprotein condensates (bodies) indicates a cotranslational entry of the CPY into these membranes. The secondary transfer of a portion of CPY into vacuoles is probably mediated by the lipoprotein uptake process.
Keywords: Histocytochemistry; elektronová mikroskopie; histocytochemie; Freeze Etching; Lipoproteins; karboxypeptidasy; Aminopeptidases; leptání mrazem; kathepsin A; Microscopy, Electron; Alkaline Phosphatase; Endoplasmic Reticulum; Vacuoles; endoplazmatické retikulum; alkalická fosfatasa; Saccharomyces cerevisiae - proteiny; Saccharomyces cerevisiae; Cathepsin A; mutace; adenosintrifosfatasy; Adenosine Triphosphatases; Mutation; aminopeptidasy; Carboxypeptidases; lipoproteiny; vakuoly; Saccharomyces cerevisiae Proteins